Wheat growing, flour milling and bread baking: A case study of a domestic agricultural industry adapting to overseas competition. Report to the foundation for Research Science and Technology - Michael Pickford (New Zealand Institute of Economic Research (NZIER), 1999)
The wheat growing, flour milling and bread baking industries (henceforth, for the sake of brevity, 'the industries') are closely interrelated in various ways. [...] In New Zealand most wheat is grown to be milled into flour, with individual farmers usually contracting directly with particular millers for sale of their crop prior to sowing the seed. As the country is not self-sufficient in wheat, the local crop has to be supplemented by substantial imports, mostly from Australia. The bulk of the flour milled (together with a little imported flour from Australia) is used for bread baking, and most bread is now produced in the plant bakeries of the two major producers, which by vertical integration are also the major flour millers. Those same companies are also important producers of other flour-based goods, such as pastry and pies. By-products of flour milling - bran and pollard - are used in the stock feed manufacturing industry. Apart from these vertical links, all industry participants contribute through a levy system to fund research through the Crop and Food Institute and other bodies on wheat breeding and related matters, a process which over several decades has generated wheat varieties better adapted to local conditions and with improved milling and baking qualities. In addition, during the period of heavy regulation of the New Zealand economy from the 1930s to the 1980s, the wheat, flour and bread industries were the subject of especially stringent regulations which recognised their interdependence. This essay is concerned primarily with how the regulations impacted on those industries and, more especially, with how they have adapted to operating in free markets following deregulation over the period 1981-87. In section 2 we look at the history and impact of the regulation of the industries. The following section describes the huge changes in their structures triggered by deregulation, culminating in the formation of three (and more recently, two) vertically-integrated and foreign-owned milling and baking companies. Sections 4, 5, and 6 then overview the background demand and supply conditions in the wheat, flour milling, and bread baking industries respectively. Sections 7, 8, and 9 go on to review the market structures, market conduct and market performance of the industries respectively, with the prime focus being on the bread industry, the major end point of the production chain. Finally, in section 10 the conclusions are drawn together.
Keywords: 330; Weizenanbau; Mühlenindustrie; Weizenmarkt; Backgewerbe; Weizenpolitik; Neuseeland